The spatial current structure in the Indonesian Seas in November 2014, during The Expedition of Widya Nusantara (EWIN) - Adi Purwandana; Dewi Surinati; Ahmad Bayhaqi; Mochamad Furqon Aziz Ismail; Mochamad Riza Iskandar; Corry Corvianawatie; Asep Sandra Budiman; Edikusmanto; Djatmiko Irianto; Muhadjirin (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The spatial current patterns in the Indonesian seas were mapped based on a wide range of snapshot observations during the Expedition of Widya Nusantara (EWIN 2014) Leg 1 in November 2014. The current profiles were measured using the Shipboard Acoustic Doppler Current Profiler (SADCP) of the RV Baruna Jaya VIII. This study is aimed to reveal the current system in the Indonesian seas from observation. Remarkable current patterns of the Indonesian throughflow (ITF) were observed penetrating via the Mindanao Strait, southern Makassar Strait, and Lifamatola Passage, including its recirculation in the northern Maluku Sea and in the Sulawesi Sea. These results suggested that during the late Southeast Monsoon (SEM), the upper layer ITF is still significantly penetrating the Indonesian seas. The indication of anticyclonic and cyclonic circulations in the upper 50 m and lower 75 m, respectively, was also observed in the western Banda Sea